EMIRATE OF BUKHARA ON THE WORLD MARKET: 19th CENTURY - EARLY 20th CENTURY - Zamonov Akbar Turg‘unovich; Hakimova Xandona Oybek qizi (Scholars Digest Publishing, 2023)
This article discusses the development of international trade conducted by the Bukhara Emirate with neighboring countries in the second half of the 19th century and the beginning of the 20th century.
Keywords: trade, buying and selling, letter, customs, Zandani, expedition, India, Afghanistan, ambassador, Balkh, Bukhara, Russia.